PANCASILA SEBAGAI SUMBER SEGALA SUMBER HUKUM - Anik Kunantiyorini (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Indonesian people in his life since ancient times have known that didiskripsikan tuham according to each perspective, social interaction with cooperativeness and order and peace alive.  The  values  that  live,  grow  and  develop  dug  by  the  founders  of  this  country  in  1945  as  a  trial BPUPKI staatsfundamentalnorm or Groundnorm called Pancasila.  Pancasila as a system of philosophy, ideology and the basic law of the state in the governance of the state laws of the Republic of Indonesia, is placed on the list as the source of all sources of law, in the sense that all rules undangn Regulations must load and animate the values of Pancasila.  In Political Pancasila as the source of all sources of law is a political agrement. Pancasila as the source  of  all  sources  of  law  within  the  limits  of  positive  law,  because  the  law  bersumberkan  on religious teachings, rooted in revelation, as Pancasila is not religion.